The impact of nationalising the private shareholding of the South African Reserve Bank - Hauptfleisch, David C L (Department of Finance and Tax, 2019)
This paper investigates, as its main question, the probable impact of nationalising the private shareholding of the South African Reserve Bank (SARB). A sub-question is first posed in order to answer the main question. The sub-question is: are the shareholders of the SARB the owners of the Bank and what are their rights and obligations? In a nationalisation scenario the rights and obligations of the shareholders will cease to exist. Therefore, it is essential first to determine all the rights and obligations of the shareholders when measuring the impact of nationalising the SARB private shareholding. The paper uses the A.M. Honoré legal test of ownership to determine whether the shareholders of a South African listed company and the SARB shareholders, can be viewed as the owners of the respective entities. That legal test indicated that the shareholders of a JSE- listed corporation satisfy very few of the legal incidents of ownership and the SARB shareholders satisfied none. Consequently, from a legal point of view, shareholders of the SARB are not its owners. By analysing, critically, the historic data concerning share price growth and share liquidity for the SARB, and what the possible expropriation compensation might be, this paper seeks to determine if profit is a ii motive for owning SARB shares. Profit was not found to be a motive for owning those shares. The motive of shareholders in owning SARB shares can potentially reveal undisclosed shareholder rights and obligations. The AGM of the SARB is also observed to determine if any undisclosed shareholder rights and obligations exist. No unusual rights and obligations were determined except a close relationship between the commercial bank shareholders and the SARB. The SARB shareholder rights and obligations are in accordance with the South African Reserve Bank Act and Regulations. After the sub-question is answered and a complete set of shareholder rights and obligations are determined, the operational, financial and corporate governance effect of nationalising the South African Reserve Bank is discussed. If it is assumed that the directors and Monetary Policy Committee (MPC) can continue with the same degree of autonomy, then nationalising the private shareholding of the SARB will have no significant financial, operational and corporate governance effect on the Bank. This paper suggests that the true motive for requesting the nationalisation of the SARB private shareholding, is the desire to nationalise the ability of commercial banks to create the nation’s money supply.